PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS IV GUNUNGSITOLI - Peringatan Harefa; Aferiaman Telaumbanua (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
This study aims to determine how much influence career development has on employee performance at class IV Gunungsitoli port authority and port authority offices.In this study, the formulation of the problem is "Is there an influence of career development on employee performance at the Class IV Gunungsitoli Port Authority and Harbor Authority Office?". The sample in this study, due to the limited population, was taken by the entire population of 36 people. While the method used in this study is a quantitative research method (Inferest), where the data collected is verified, validated, tested for reliability and hypotheses using the t test. Processing data distribution t with dk = 34 and a significant level of 5% obtained ttable = 2.032. Thus, tcount> ttable (10.952 > 2.032), with a correlation coefficient of 0.883. The results obtained by testing the coefficient of determination is 78% The Effect of Career Development on Employee Performance, while other factors not discussed in this study are 22%. Based on the results of testing the hypothesis Ha is accepted and Ho is rejected, indicating that tcount> ttable (10,952 > 2,032), there is an effect of Career Development on Employee Performance at Class IV Gunungsitoli Port Authority and Harbormaster Office.